2019
DOI: 10.1021/acs.est.9b01446
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of the Polyamide Membrane Monomer with Free Chlorine: Reaction Kinetics, Mechanisms, and the Role of Chloride

Abstract: Aromatic polyamide thin-film composite membranes are widely used in reverse osmosis (RO) and nanofiltration (NF) due to their high water permeability and selectivity. However, these membranes undergo biofouling and can degrade and eventually fail during free chlorine exposure. To better understand this effect, the reactivity of the polyamide monomer (benzanilide (BA)) with free chlorine was tested under varying pH and chloride (Cl − ) conditions. The kinetic results indicated that the current existing mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 48 publications
4
33
1
Order By: Relevance
“…In the end, this procedure was the primary one used to measure these compounds since no N-halogenated byproducts (e.g., N-Br-BA or N-Cl-BA) were present in any of the experiments. These N-halogenated byproducts were of concern since N-Cl-BA was previously observed to revert back to its unhalogenated form when quenched by phenol or SO 3 2− , 20 and a similar outcome was expected for N-Br-BA. Their absence was confirmed by crossvalidating byproduct formation through two experiments, which are described in detail in Text S4.…”
Section: ■ Materials and Methodsmentioning
confidence: 70%
See 4 more Smart Citations
“…In the end, this procedure was the primary one used to measure these compounds since no N-halogenated byproducts (e.g., N-Br-BA or N-Cl-BA) were present in any of the experiments. These N-halogenated byproducts were of concern since N-Cl-BA was previously observed to revert back to its unhalogenated form when quenched by phenol or SO 3 2− , 20 and a similar outcome was expected for N-Br-BA. Their absence was confirmed by crossvalidating byproduct formation through two experiments, which are described in detail in Text S4.…”
Section: ■ Materials and Methodsmentioning
confidence: 70%
“…20 Our previous results provided evidence that the Orton rearrangement (Scheme 1a) did not occur during chlorination, which along with these additional studies casts a further doubt as to whether it is involved during bromination as well. 20 In contrast, one study found that N-Br-acetanilide directly transformed to para-Br-acetanilide more easily than its corresponding chlorinated analogue (e.g., N-Cl-acetanilide) 35 (eq 12), initially suggesting that the Orton rearrangement could occur (Scheme 1a). Notably, this reaction took place in non-dissociating solvents (e.g., benzene) (eq 12) 35 that likely prohibited the formation of ionized species, such as Br − , which might be required for the Orton rearrangement to occur, as observed for its analogous Cl − (Scheme 1a).…”
Section: Hocl Brmentioning
confidence: 78%
See 3 more Smart Citations